A New Species of Cerambycid, Epania alveolaris Sp. Nov. from Betta, Bihar, India - Chatterjee, P. N.; Misra, M. P. (Indian Forester, 1969)
Epania alveolaris sp. nov., is described from Betta, Bihar (India).